Implementation of Judge Independence in the Process of Implementing Justice in Islamic Law Perspective - Khairul Huda; Bambang Tri Bawono; Achmad Arifullah (Universitas Islam Sultan Agung, 2022)
This study aims to analyze and examine the implementation of the independence of judges in the process of administering justice in Indonesia and to understand and examine the implementation of the independence of judges in the administration of justice from an Islamic perspective. This study uses library research methods or library research that is